Bargaining with patriarchy through the life course: obstacles faced (and overcome) by women leaders in Kerala's health sector - Devaki Nambiar; Gloria Benny; Hari Sankar D (BMC, 2022)
Abstract Background The COVID-19 pandemic has helped shine the spotlight on the role of women's leadership in tackling the world's health and health system challenges. The proportion of women occupying senior leadership positions in the health sector is less compared to males, even as they constitute a vast majority of the work force. The South Indian state of Kerala is an exception to this trend, a phenomenon that we sought to understand and contextualise. We undertook a study to understand the personal and professional journeys of some women leaders in the Kerala health sector to determine the antecedents of their leadership positions, the challenges that came their way in leadership, and strategies adopted to overcome these challenges. We also investigated into how these experiences shaped their styles and approaches to leadership. Methods We conducted a qualitative study involving semi-structured in-depth interviews with women leaders. Sixteen women leaders were identified from public records and through peer nomination and interviewed in their language of preference following written informed consent procedures. Interviews focused on participants' professional and personal trajectories, work-life balance, style of leadership, challenges, enablers, lessons learned in their path, and their vision for the health system. The interviews conducted in Malayalam were transliterated into English and thematically analysed using Atlas.Ti8 software by three researchers. Results Our study participants were aged 40 to around 80 years, from 8 out of 14 districts of the state. Women leaders in Kerala's health sector faced challenges through the life-course: during their early school education, in professional service as well as in their roles as leaders. There were myriad experiences - including gender stereotyping and discrimination at the intersection of gender and other social identities. Women developed manifold ways of overcoming them and evolve unique - and again myriad-leadership styles. Conclusions Women leaders in Kerala have faced shared challenges through their life-course to climb up the ranks of leadership; each leader has adopted unique ways of overcoming them and developed similarly unique leadership styles. At each life stage there were bargains with patriarchy - involving family members (often as allies), against formal and informal institutional rules, managers, peers and subordinates., which in turn suggests a feminist consciousness on the part of Kerala women leaders as well as the society in which they are seeking to lead.